2019
DOI: 10.1016/j.fertnstert.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a novel flexible progestin primed ovarian stimulation protocol and the flexible gonadotropin-releasing hormone antagonist protocol for assisted reproductive technology

Abstract: Objective: To determine whether a flexible progestin primed ovarian stimulation (fPPOS) protocol is effective for preventing premature ovulation. Design: Retrospective cohort study. Setting: Private assisted reproduction center. Patient(s): Eighty-seven oocyte donors and 191 recipients of fresh oocytes. Intervention(s): Each donor was stimulated with a flexible gonadotropin-releasing hormone (GnRH) antagonist protocol in one cycle and with the new fPPOS protocol in the other, within a period of 6 months. FSH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 28 publications
5
53
1
Order By: Relevance
“…There has been controversy about whether the use of MPA in the PPOS program will affect the outcome of pregnancy. However, the literature in recent years has all related to the safety and effectiveness of the PPOS scheme [38]. It is suggested that the numbers of blastocysts and euploid blastocysts per patient and the number of euploid embryos per injected oocyte are similar for patients undergoing the PPOS program and for those undergoing COS with GnRH antagonists [39].…”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy about whether the use of MPA in the PPOS program will affect the outcome of pregnancy. However, the literature in recent years has all related to the safety and effectiveness of the PPOS scheme [38]. It is suggested that the numbers of blastocysts and euploid blastocysts per patient and the number of euploid embryos per injected oocyte are similar for patients undergoing the PPOS program and for those undergoing COS with GnRH antagonists [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a few studies have also compared the antagonist protocol with PPOS. 15,30,31 Iwami et al compared the antagonist protocol and PPOS and obtained similar results in normo-responsive patients. 15 Begueria et al performed a non-inferiority trial to compare MPA and GnRH antagonist with regard to the number of mature oocytes retrieved in oocyte donation cycles, and reported no differences in the number of mature oocytes, length of stimulation, fertilization rate, or quality of embryos between the two treatments.…”
Section: Discussionmentioning
confidence: 89%
“…They reported similar cleavage, blastulation, implantation and live birth rates in both groups. 31 Most studies have included normo-responsive patients. 18,25 However, hyper-responsive patients may be the most suitable population for this protocol because freeze-all is the current standard of care for preventing OHSS in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous investigation, the fertility potential of oocytes collected in the presence of exogenous progestogen, regardless of MPA [8,12], dydrogesterone [10,27,34], or utrogestan [9,13,36], are as competent as those collected via conventional stimulation protocols. An interesting big data revealed no difference in the reproductive outcome of the oocytes induced in the presence or absence of levonorgestrel-releasing intrauterine device [37].…”
Section: Resultsmentioning
confidence: 99%
“…Recipients of fresh oocytes from fPPOS and GnRH antagonist cycles had similar cleavage, implantation, and live birth/ongoing pregnancy rates [34]. As to PPOS versus long protocol which suppresses pituitary function much more than short and antagonist protocol, there was a retrospective self-controlled study conducted on 104 aged infertile patients who failed in their first IVF/ICSI attempt by means of long protocol.…”
Section: Resultsmentioning
confidence: 99%